Influence of hydration and electrolyte supplementation on incidence and time to onset of exercise-associated muscle cramps - Jung, A. P.; Bishop, P. A.; Al-Nawwas, A.; Dale, R. B. (Journal of Athletic Training, 2005)
Context: Exercise-associated muscle cramps (EAMCs) are common among physically active individuals and are temporarily disabling; therefore, prevention is of great interest.